Functional Status of Neonatal and Pediatric Patients After Extracorporeal Membrane Oxygenation*. Issue 6 (June 2017) - Cashen, Katherine; Reeder, Ron; Dalton, Heidi J.; Berg, Robert A.; Shanley, Thomas P.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Carcillo, Joseph; Harrison, Rick; Dean, J. Michael; Jenkins, Tammara; et al.
Abstract : Objectives: To describe functional status at hospital discharge for neonatal and pediatric patients treated with extracorporeal membrane oxygenation, and identify factors associated with functional status and mortality. Design: Secondary analysis of observational data collected by the Collaborative Pediatric Critical Care Research Network between December 2012 and September 2014. Setting: Eight hospitals affiliated with the Collaborative Pediatric Critical Care Research Network. Patients: Patients were less than 19 years old and treated with extracorporeal membrane oxygenation. Interventions: Functional status was evaluated among survivors using the Functional Status Scale. Total Functional Status Scale scores range from 6 to 30 and are categorized as 6–7 (good), 8–9 (mildly abnormal), 10–15 (moderately abnormal), 16–21 (severely abnormal), and greater than 21 (very severely abnormal). Measurements and Main Results: Of 514 patients, 267 (52%) were neonates (⩽ 30 d old). Indication for extracorporeal membrane oxygenation was respiratory for 237 (46%), cardiac for 207 (40%), and extracorporeal cardiopulmonary resuscitation for 70 (14%). Among 282 survivors, 89 (32%) had good, 112 (40%) mildly abnormal, 67 (24%) moderately abnormal, and 14 (5%) severely or very severely abnormal function at hospital discharge. Among neonates, development of renal failure and longer hospitalization were independently associated with worse Functional Status Scale. Chronic conditions, prematurity, venoarterial extracorporeal membrane oxygenation, increased red cell transfusion in the first 24 hours of extracorporeal membrane oxygenation, and longer extracorporeal membrane oxygenation duration were independently associated with mortality. Among pediatric patients, chronic neurologic conditions, tracheostomy or home ventilator, extracorporeal cardiopulmonary resuscitation, hepatic dysfunction, and longer ICU stay were independently associated with worse Functional Status Scale. Chronic cardiac conditions, hepatic dysfunction, and neurologic or thrombotic complications were independently associated with mortality. Achieving blood lactate concentration less than or equal to 2 mmol/L during extracorporeal membrane oxygenation was independently associated with survival in both neonatal and pediatric patients. Conclusions: In this study, about half of extracorporeal membrane oxygenation patients survived with good, mildly abnormal, or moderately abnormal function at hospital discharge. Patient and extracorporeal membrane oxygenation-related factors are associated with functional status and mortality. Abstract : Supplemental Digital Content is available in the text.